Factors Affecting Mobile Tagging Awareness; A Research on Social Media Consumers - DALDAL, Kübra; KILIÇ, Sabiha (Journal of Economic Development, Environment and People, 2014)
The purpose of the study is to identify the factors affecting awareness of mobile tagging on social media. The study assumes that the mobile tagging awareness levels of social media consumers are high. As a result of the literature review made in the scope of the purpose and assumption of the study, it was identified that the variables used in the measurement of brand awareness levels are recognition, remembering, being first in remembering, brand dominance, brand knowledge and brand opinion. A conceptual model showing the relation between these variables and mobile tagging awareness levels of social media consumers and hypotheses connected to this model were developed and a survey form, loyal to the relevant literature, was prepared in order to obtain the data necessary for the analyses. The universe of the study covers the consumers who are members of social media sites Facebook, Twitter and Linked In. For the analysis of the data obtained as a result of the survey conducted, descriptive statistics containing percentages and frequencies, factor analysis and Pearson’s Correlation Coefficient was used in the analysis of the hypotheses.